The In Vitro Anti-Parasitic Activities of Emodin toward Toxoplasma gondii - Oluyomi Stephen Adeyemi; Kosei Ishii; Kentaro Kato (MDPI AG, 2023)
Currently, toxoplasmosis affects nearly one-third of the world's population, but the available treatments have several limitations. This factor underscores the search for better therapy for toxoplasmosis. Therefore, in the current investigation, we investigated the potential of emodin as a new anti-Toxoplasma gondii while exploring its anti-parasitic mechanism of action. We explored the mechanisms of action of emodin in the presence and absence of an in vitro model of experimental toxoplasmosis. Emodin showed strong anti-T. gondii action with an EC50 value of 0.03 µg/mL; at this same effective anti-parasite concentration, emodin showed no appreciable host cytotoxicity. Likewise, emodin showed a promising anti-T. gondii specificity with a selectivity index (SI) of 276. Pyrimethamine, a standard drug for toxoplasmosis, had an SI of 2.3. The results collectively imply that parasite damage was selective rather than as a result of a broad cytotoxic effect. Furthermore, our data confirm that emodin-induced parasite growth suppression stems from parasite targets and not host targets, and indicate that the anti-parasite action of emodin precludes oxidative stress and ROS production. Emodin likely mediates parasite growth suppression through means other than oxidative stress, ROS production, or mitochondrial toxicity. Collectively, our findings support the potential of emodin as a promising and novel anti-parasitic agent that warrants further investigation.